Species of Anastrepha (Diptera: Tephritidae) captured in a guava orchard (Psidium guajava L., Myrtaceae) in Boa Vista, Roraima, Brazil - Marsaro, Alberto Luiz; Deus, Ezequiel da Glória de; Ronchi-Teles, Beatriz; Adaime, Ricardo; Silva, R. J. (Revista Brasileira de Biologia, 2013)
The guava fruit (Psidium guajava) is among the most strongly affected by fruit flies in Brazil. In the Brazilian Amazon, 11 species of Anastrepha have been reported in guava orchards to date. This work aimed to identify the species of Anastrepha present in a guava orchard in the municipality of Boa Vista, determine the species infesting the fruits, and identify any parasitoids present. Two McPhail traps with food bait were installed and weekly collections were made between January and December 2008. Fruits were also collected systematically during this period, with a view to determining the association between host plant and tephritid species. Nine species of Anastrepha were identified, in addition to one specimen belonging to a probable new species. Anastrepha striata Schiner, Anastrepha sororcula Zucchi, Anastrepha obliqua (Macquart), and Anastrepha fraterculus (Wiedemann) were the dominant species in the orchard, accounting for 84.8% of all captured individuals. All females collected directly from fruits were A. striata. Doryctobracon areolatus (Szépligeti) was the only parasitoid species obtained. In this work, Anastrepha ethalea (Walker) is reported for the first time in the state of Roraima.
Espécies de Anastrepha (Diptera: Tephritidae) capturadas em pomar de goiabeira (Psidium guajava L., Myrtaceae) em Boa Vista, Roraima, Brasil
Keywords: Animals; Classification; Female; Male; Parasitology; Psidium; Tephritidae; Animal; Female; Male; Psidium; Tephritidae